Accelerate Reduction of Stunting: Knowledge and Parenting Patterns of Parents with Stunting Toddler in Kendal District - Dona Yanuar Agus Santoso; Livana PH (GLOBAL HEALTH SCIENCE GROUP, 2023)
Kendal Regency emerges as a significant stunting hotspot, reporting 5,017 at-risk toddlers for stunting in 2021. Parental comprehension of stunting and caregiving practices in toddler nutrition are crucial predisposing factors. This study investigates parental knowledge and caregiving patterns regarding stunted toddlers in Kendal. Employing purposive sampling, 165 parents (mothers/fathers) were selected. Through a knowledge and caregiving pattern questionnaire, findings reveal parents' moderate awareness of toddler stunting; 77.6% display satisfactory understanding, while 22.4% demonstrate limited awareness. Analysis of caregiving patterns indicates that 57% of parents adopt appropriate nutritional caregiving, 27.9% exhibit insufficiencies, and 15.2% follow commendable practices. These results underscore the need to enhance parental understanding of stunting and improve nutritional caregiving for stunted children. It is recommended that parents of stunted toddlers actively seek information on stunting management and attentively address nutritional requirements, particularly fat intake, for severely underweight children.